2021
DOI: 10.1038/s41388-021-01672-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of low-frequency variants of UGT1A3 associated with bladder cancer risk by next-generation sequencing

Abstract: Although genome-wide association studies (GWASs) have successfully revealed many common risk variants for bladder cancer, the heritability is still largely unexplained. We hypothesized that low-frequency variants involved in bladder cancer risk could reveal the unexplained heritability. Next-generation sequencing of 113 patients and 118 controls was conducted on 81 genes/ regions of known bladder cancer GWAS loci. A two-stage validation comprising 3,350 cases and 4,005 controls was performed to evaluate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…UGT1A3 encodes a vital protein of the human UDP-glucuronosyltransferase (UGT) superfamily performing a key role in endobiotic and xenobiotic metabolism. Many studies showed that UGT1A3 was related to many kinds of cancers including pancreatic cancer [ 34 ], bladder cancer [ 16 ], thyroid cancer [ 35 ], stomach cancer [ 36 ], colorectal cancer, colon cancer [ 37 ], and lung adenocarcinoma [ 38 ]. Zheng et al [ 16 ] first revealed that a low-frequency variant rs28898617 in UGT1A3 was significantly associated with the increased risk of BCa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UGT1A3 encodes a vital protein of the human UDP-glucuronosyltransferase (UGT) superfamily performing a key role in endobiotic and xenobiotic metabolism. Many studies showed that UGT1A3 was related to many kinds of cancers including pancreatic cancer [ 34 ], bladder cancer [ 16 ], thyroid cancer [ 35 ], stomach cancer [ 36 ], colorectal cancer, colon cancer [ 37 ], and lung adenocarcinoma [ 38 ]. Zheng et al [ 16 ] first revealed that a low-frequency variant rs28898617 in UGT1A3 was significantly associated with the increased risk of BCa.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that UGT1A3 was related to many kinds of cancers including pancreatic cancer [ 34 ], bladder cancer [ 16 ], thyroid cancer [ 35 ], stomach cancer [ 36 ], colorectal cancer, colon cancer [ 37 ], and lung adenocarcinoma [ 38 ]. Zheng et al [ 16 ] first revealed that a low-frequency variant rs28898617 in UGT1A3 was significantly associated with the increased risk of BCa. However, in this study, we failed to replicate the association between SNPs of UGT1A3 and BCa in the Chinese Northeast population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allele was only observed in the Asian population, but monomorphism was also observed in the Europeans. The total allele frequency was estimated to be 0.003 [ 253 ].…”
Section: Pharmacogenomics Of Metabolismmentioning
confidence: 99%
“…Multiple recent reports have highlighted that the expression of UGT enzymes and alternative variants is frequently perturbed in disease conditions and especially in tumors [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In fact, metabolic alterations constitute one well documented strategy exploited by cancer cells to sustain rapid cell proliferation and evasion.…”
Section: Introductionmentioning
confidence: 99%